Psychiatric Sequelae of Dengue: A Review of the Interface - Priyanka Renita D’Souza; Debora Sona D’Silva (Journal of Tropical Medicine)
Dengue is one of the major public health concerns in tropical and subtropical countries. In addition to neurological sequelae which are well documented, emerging evidence suggests that dengue may also lead to psychiatric sequelae including mood disorders, psychosis, anxiety, and body dysmorphic disorder. This narrative review aims to synthesize the existing literature to explore the psychiatric manifestations and postulated pathophysiological mechanisms and identify predictors and treatment of psychiatric sequelae in dengue. This review identified 30 studies including observational studies, case reports, and case series. The immune-inflammatory responses due to cytokine dysregulation, blood–brain barrier disruption, direct viral effects, and epigenetic mechanisms with histone deacetylase activation are possible contributors to psychiatric sequelae in dengue. The main predictors include severity of dengue, thrombocytopenia, central nervous system involvement, febrile and critical phase of illness, specific dengue virus serotypes (DENV-2 and DENV-3), and stress due to hospitalization. Psychiatric symptoms often persist beyond the acute phase, highlighting the importance of long-term follow-up to evaluate the impact of dengue on mental health. Additionally, comparisons with other Flaviviridae viruses, such as Zika, West Nile, and Japanese encephalitis viruses, reveal both shared and distinct psychiatric implications, suggesting potential virus-specific mechanisms. The current treatment approaches are largely extrapolated from general psychiatric practice, with limited research on targeted interventions. Future research should focus on standardized diagnostic assessment, longitudinal follow-up, diagnostic biomarkers, and developing targeted treatment strategies to improve clinical outcomes. With rising cases of dengue, integrating psychiatric screening into routine dengue management may enhance early recognition and intervention. Hence, a multidisciplinary research approach involving psychiatrists, neurologists, infectious disease specialists, immunologists, and policymakers is crucial for addressing psychiatric sequelae in dengue fever and mitigating the detrimental implications on public health.